Обґрунтування основних параметрів пульсатора пневмоімпульсної машини для сепарації насіння за густиною - Петренко, М. М.; Богатирьов, Д. В.; Онопа, В. В. (КНТУ, 2006)
В статті наведено аналітичні формули для визначення основних параметрів та режимів роботи пульсатора пневмоімпульсної машини для сепарації насіння за густиною. Обґрунтовано отримані формули щодо визначення параметрів пульсатора, також подано порядок їх розрахунку з експериментальним підтвердженням у вигляді номограми. The thesis is developed the problem to pneumatic-impulsive separation according to density. Analytical researches are conducted and the determined mathematical model of motion of particle is got during pneumatic-impulsive separation and formula for determination of resistance of pulsator, frequency of pulsation, height of establishment of divizors, and also speed of filtration.Experimental researches confirmed expedience of the use of pulsator by setting of him in a pneumatic channel for replacement of swaying motion of sounding board on a pulsating blast.
Keywords: процес сепарації в стані псевдозрідження; пневмоімпульсна машина; пульсатор; пульсуючий потік повітря